1987
DOI: 10.1159/000118359
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Distress and Prognosis of Psychotic Illness

Abstract: The medical histories of a group of 511 patients hospitalized for schizophrenia were examined for the occurrence of perinatal distress. These patients were part of a 40-year follow-up study, so that their prognostic outcome was known at the time of this study. In this way, 200 cases of chronic schizophrenia were compared with 311 cases of psychotics with good prognosis. It was found that a history of perinatal distress was much more common in the poor prognosis group than in the good prognosis group. This diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 15 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Recent studies investigating the role of PBCs in schizophrenia have reported increased rates of PBCs in people with schizophrenia when compared to: (1) unrelated controls (Pollock & Greenberg 1966;McNeill & Kaij 1978;Jacobsen & Kinney 1980;Wilcox & Nasrallah 1987;Foerster et al 1991;O'Callaghan et al 1992;Mednick 1994;Verdoux & Bourgeois 1993;Buka et al 1993); (2) siblings and/or other family members (Woemer et al 1973;Pamas et al 1982;deLisi et al 1988;Goodman & Emroy 1992;Huen & Maier 1993); (3) co-twins (Stabenau et al 1967;Bracha et al 1992;Onstad et al 1992). The findings of studies investigating the role of PBCs suggest that such complications are important in the aetiology of schizophrenia.…”
Section: Pregnancy and Birth Complications In Schizophreniamentioning
confidence: 99%
“…Recent studies investigating the role of PBCs in schizophrenia have reported increased rates of PBCs in people with schizophrenia when compared to: (1) unrelated controls (Pollock & Greenberg 1966;McNeill & Kaij 1978;Jacobsen & Kinney 1980;Wilcox & Nasrallah 1987;Foerster et al 1991;O'Callaghan et al 1992;Mednick 1994;Verdoux & Bourgeois 1993;Buka et al 1993); (2) siblings and/or other family members (Woemer et al 1973;Pamas et al 1982;deLisi et al 1988;Goodman & Emroy 1992;Huen & Maier 1993); (3) co-twins (Stabenau et al 1967;Bracha et al 1992;Onstad et al 1992). The findings of studies investigating the role of PBCs suggest that such complications are important in the aetiology of schizophrenia.…”
Section: Pregnancy and Birth Complications In Schizophreniamentioning
confidence: 99%
“…It is interesting, therefore, that males with schizophrenia are more likely than their female counterparts to have a history of OCs (Wilcox and Nasrallah 1987; Pearlson et al 1989; Foerster et al 1991 b , 1991 c ). Furthermore, males are more likely to exhibit structural brain abnormalities than females; Castle and Murray (1991 a ) reviewed 10 imaging studies (6 CT and 4 MRI) that report this.…”
Section: Gendermentioning
confidence: 99%
“…In schizophrenic populations, males are more likely to have a history of obstetric complications than are females (Pearlson et al 1985;Wilcox & Nasrallah, 1987;Owen et al 1988;Foerster et al 1991ft). This is consonant with the fact that structural brain anomalies have been reported more commonly in male than female schizophrenics (see Table 1).…”
Section: Brain Abnormalities In Schizophrenic Malesmentioning
confidence: 99%